The role of self-efficacy and parental influence in the interest of a career in accounting students in the field of taxation - Chaerunisak, Uum Helmina; Prastyatini, Sri Lestari Yuli; Listyawati, Reni; Wafiroh, Rifah Ayu; Mujiyanti, Sri (Proceeding International Conference on Accounting and Finance, 2024)
This research is motivated by the phenomenon of students’ lack of interest in pursuing a career in taxation, while the Indonesian government needs student graduates who have an interest in a career in taxation and graduates who are competent in taxation. This research aims to determine the influence of self-efficacy and parental influence on accounting students’ career interest in taxation, partially or simultaneously. This research method uses quantitative descriptive methods and primary data using questionnaires. The sampling technique uses purposive sampling technique. This research used a sample of private university students in the city of Yogyakarta. This research succeeded in collecting 100 respondents. Tools for processing data using IBM SPSS version 20. The results of this research show that both simultaneously and partially self-efficacy and parental influence influence accounting students’ career interest in taxation by 69.9%, while the remaining 30.1% is influenced by other factors outside the variables of this research.